Cost-Effectiveness of Treatments for Musculoskeletal Conditions Offered by Physiotherapists: A Systematic Review of Trial-Based Evaluations - Linda Baumbach; Wiebke Feddern; Benedikt Kretzler; André Hajek; Hans-Helmut König (Sports Medicine - Open, 2024)
Abstract Background Musculoskeletal conditions are a leading contributor to disability worldwide. The treatment of these conditions accounts for 7% of health care costs in Germany and is often provided by physiotherapists. Yet, an overview of the cost-effectiveness of treatments for musculoskeletal conditions offered by physiotherapists is missing. This review aims to provide an overview of full economic evaluations of interventions for musculoskeletal conditions offered by physiotherapists. Methods We systematically searched for publications in Medline, EconLit, and NHS-EED. Title and abstracts, followed by full texts were screened independently by two authors. We included trial-based full economic evaluations of physiotherapeutic interventions for patients with musculoskeletal conditions and allowed any control group. We extracted participants' information, the setting, the intervention, and details on the economic analyses. We evaluated the quality of the included articles with the Consensus on Health Economic Criteria checklist. Results We identified 5141 eligible publications and included 83 articles. The articles were based on 78 clinical trials. They addressed conditions of the spine (n = 39), the upper limb (n = 8), the lower limb (n = 30), and some other conditions (n = 6). The most investigated conditions were low back pain (n = 25) and knee and hip osteoarthritis (n = 16). The articles involved 69 comparisons between physiotherapeutic interventions (in which we defined primary interventions) and 81 comparisons in which only one intervention was offered by a physiotherapist. Physiotherapeutic interventions compared to those provided by other health professionals were cheaper and more effective in 43% (18/42) of the comparisons. Ten percent (4/42) of the interventions were dominated. The overall quality of the articles was high. However, the description of delivered interventions varied widely and often lacked details. This limited fair treatment comparisons. Conclusions High-quality evidence was found for physiotherapeutic interventions to be cost-effective, but the result depends on the patient group, intervention, and control arm. Treatments of knee and back conditions were primarily investigated, highlighting a need for physiotherapeutic cost-effectiveness analyses of less often investigated joints and conditions. The documentation of provided interventions needs improvement to enable clinicians and stakeholders to fairly compare interventions and ultimately adopt cost-effective treatments.